Prediction of the Binding to the Nuclear Factor NF-Kappa-B by Constituents from Teucrium polium L. Essential Oil - Renilson Castro de Barros; Renato Araújo da Costa; Nesrine Guenane; Boulanouar Bakchiche; Farouk Benaceur; Omer Elkiran; Suelem Daniella Pinho Farias; Vanessa Regina Silva Mota; Maria Fani Dolabela (Current Issues in Molecular Biology)
Teucrium polium L. is a plant with various claims of ethnobotanical use, primarily for inflammatory diseases. Chemical studies have already isolated different types of terpenes from the species, and studies have established its pharmacological potential. The present study evaluates the components of T. polium essential oil cultivated in the Algerian Saharan Atlas. GC-MS identified the major components as fenchone (31.25%), 3-carene (15.77%), cis-limonene oxide (9.77%), and myrcene (9.15%). In the in silico prediction, molecules with more than 1% abundance were selected. Regarding Lipinski’s rule, all molecules followed the rule. All molecules were found to be toxic in at least one model, with some molecules being non-genotoxic (6, 8, 10, 11, 12, 13) and others being non-mutagenic (5, 7, 9, 14). Three molecules were selected that showed the best results in pharmacokinetic and toxicity studies: the molecules that did not present carcinogenic potential (7—myrtenal; 9—myrtenol; 14—verbenol). The molecular target was established, and it seems that all three bound to the nuclear factor NF-kappa-B. Based on the docking and molecular dynamics results, these molecules have potential as anti-inflammatory and antitumor therapies, with further in vitro and in vivo studies needed to evaluate their activity and toxicity.